1961
DOI: 10.5962/bhl.part.9822
|View full text |Cite
|
Sign up to set email alerts
|

The crane fly genus Dolichopeza in North America

Abstract: PAGE johnsonella 814 obscura 822 polita polita 833 polita pratti 840 polita cornuta new subspecies 845 sayi 850 similis 858 subalbipes 864 subvenosa 873 tridenticiilata 879 venosa 887 walleyi 894 Summary and conclusions 905 Literature cited 920 * Curtis' British Entomology is a series of colored plates, 770 in all, accompanied by descriptive notes. Published in London, these plates were issued a few each month from 1823 to 1840. * Polyvinyl alcohol is a plastic prepared from PVA powder (I use DuPont "Elvanol,"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

1968
1968
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 1 publication
2
59
1
Order By: Relevance
“…These peaks appeared attributable to oviposition by adult chironomids which emerged twice during the study, as indicated by the dramatic seasonal increase in densities of pupating chironomids. This illustrates the importance of bryophytes to adult invertebrates for oviposition, as found by Alexander (1920), Byers (1961), Glime (1968) and Gerson (1972). The use of these plants as egg-laying sites may also explain the often high densities of small instar larvae observed in both this study (Suren 1990) and in others (e.g.…”
Section: Discussionmentioning
confidence: 59%
“…These peaks appeared attributable to oviposition by adult chironomids which emerged twice during the study, as indicated by the dramatic seasonal increase in densities of pupating chironomids. This illustrates the importance of bryophytes to adult invertebrates for oviposition, as found by Alexander (1920), Byers (1961), Glime (1968) and Gerson (1972). The use of these plants as egg-laying sites may also explain the often high densities of small instar larvae observed in both this study (Suren 1990) and in others (e.g.…”
Section: Discussionmentioning
confidence: 59%
“…If morphological constraints confine L. hudsoni larvae to this habitat, then it is presumably advantageous for them to be able to consume as many of the alternative food sources found there as possible, including the bryophytes themselves. Alternatively, tipulid larvae may have evolved a close food-association with bryophytes such that their distribution is constrained to areas where their food occurs (e.g., Alexander 1920;Byers 1961;Prichard 1983;Wyatt& Stonebumer 1989).…”
Section: Plantmentioning
confidence: 99%
“…There have been relatively few reports of nematodes associated with the more than 14 000 species of Tipuloidea worldwide and most of these have been thelastomatids, which are gut parasites (see Poinar, 1975). Byers (1983) reported an apparently phoretic association between the snow fly, Chionea alexandriana Garrett, from an abandoned nest of the pack rat, Neotoma cinerea (Ord), in Northern California and an undescribed species of Rhabditis which, as a gravid female, apparently lays an egg mass or wraps itself around the neck of a dispersing fly to gain transportation to the next rat nest. Until recently, Myolaimus was not known to be associated with insects at all (Giblin-Davis, 1997) and was reported mostly in association with moist or aquatic environments and rotting timber or vegetation, including compost piles (Hirschmann, 1952;Paesler, 1956;Andrássy, 1959).…”
mentioning
confidence: 99%